Analysis of transgenic wild rice : molecular confirmation of transgene presence and risk assessment for pollen viability / Alireza Saeidi. - Saeidi, Alireza (2011)
Rice is one of the major sources of food for the population of the world, and almost 50% of the world population depends on it. Malaysian national rice production was estimated to provide just 60-65% of the domestic requirement, so the strategies that can help to increase rice yield are necessary for the agricultural sector of Malaysia. Towards this, one useful research approach is to reduce or knock down expression of a rice gene using RNA interference (RNAi) with the goal of obtaining a phenotype that is suggestive of its function. This project is a based on the analysis of RNAi “knock down” transgenic rice which has been previously developed to determine function of the putative CLAVATA1 (CLV1) receptor kinase-like protein gene from Malaysian wild rice Oryza rufipogon rice (IRGC105491). Putative transgenic plants from the T1 and T2 generations were analyzed in two main respects. The first was the determination of the segregation analysis in T1 plants by PCR detection and Southern hybridization, and the second was the assessment of pollen viability using staining and microscopy towards establishment of biosafety data for these plants. The segregation analysis of T1 plants revealed that most of the transgenic lines showed 3:1 Mendel’s segregation ratio whereas there was only one line that deviated from this ratio. The optimization of the Southern blot hybridization, for detection of transgene copy number, was performed successfully for the positive control however this was not reproducible for the plant samples with only one time that two bands were observed on the nylon membrane after detection step. After several attempts, the southern blotting procedure was not attempted further because of the time limitation of the project and also the lack of support for the necessary extra expenditure for supplying new materials. This study also concluded that pollen viability did not vary with the presence of this transgene, as the control untransformed plants and transgenic plants showed the same attributes from the pollen viability point of view. This study has established the groundwork for further studies with transgenic O. rufipogon, an important wild rice variety in Malaysia.